1996
DOI: 10.1524/ract.1996.74.special-issue.87
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Uranium in Seepage Waters of a Mine Tailing Pile Studied by Time-Resolved Laser-Induced Fluorescence Spectroscopy (TRLFS)

Abstract: Chemical speciation of U(VI) in natural seepage water and corresponding model solutions was investigated by time-resolved laser-induced fluorescence spectroscopy. Calculations of uranium speciation in this medium show that U0 2 (C0 3 )3~ and U0 2 (C0 3 )|" should be the major individual components. Due to the very low fluorescence intensity, the pure uranyl carbonato complexes could not be measured directly by TRLFS. However, a uranium fluorescence spectrum was recorded from seepage water samples. The TRLFS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
152
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(172 citation statements)
references
References 4 publications
19
152
0
1
Order By: Relevance
“…For example, Gudavalli et al (2013) showed that during dissolution of Na-and Ca-autunite, buffered bicarbonate solutions were undersaturated thermodynamically with respect to becquerelite, and uranyl carbonate and Ca-uranyl carbonate complexes were the predominant aqueous species, which were postulated to control mineral dissolution. Uranyl carbonate and alkaline-earth uranyl carbonate complexes are highly soluble and stable species that dominate the uranyl aqueous speciation between pH 7 and 11 (Bernhard et al, 1996;Kalmykov and Choppin, 2000;Bernhard et al, 2001) and also uranyl adsorption onto sediment and soils (Stewart et al, 2010). Indeed, breakthrough of U(VI) was noticeably retarded by sorption to quartz in control columns with low carbonate BPW compared to high carbonate BPW systems (Control 2, Fig.…”
Section: Effect Of Dissolved Carbonate On Dissolution Mechanismmentioning
confidence: 98%
“…For example, Gudavalli et al (2013) showed that during dissolution of Na-and Ca-autunite, buffered bicarbonate solutions were undersaturated thermodynamically with respect to becquerelite, and uranyl carbonate and Ca-uranyl carbonate complexes were the predominant aqueous species, which were postulated to control mineral dissolution. Uranyl carbonate and alkaline-earth uranyl carbonate complexes are highly soluble and stable species that dominate the uranyl aqueous speciation between pH 7 and 11 (Bernhard et al, 1996;Kalmykov and Choppin, 2000;Bernhard et al, 2001) and also uranyl adsorption onto sediment and soils (Stewart et al, 2010). Indeed, breakthrough of U(VI) was noticeably retarded by sorption to quartz in control columns with low carbonate BPW compared to high carbonate BPW systems (Control 2, Fig.…”
Section: Effect Of Dissolved Carbonate On Dissolution Mechanismmentioning
confidence: 98%
“…Inclusion of Ca, however, results in two ternary calcium-uranyl-carbonato species, CaUO 2 (CO 3 ) 3 2-and Ca 2 UO 2 (CO 3 ) 3 , emerging as dominant aqueous species, often accounting for >99% of U(VI) in solution (Bernhard et al, 1996(Bernhard et al, , 2001Kalmykov and Choppin, 2000;Kelly et al, 2003;Dong and Brooks, 2006).…”
Section: +mentioning
confidence: 99%
“…One drawback of TRLFS is that fluorescence intensity decreases with increasing pH (from pH 5.5) and ionic strength at low U concentrations (<30 µg l -1 ). The determination of higher uranyl carbonate species (UO 2 [CO 3 ] 2 2-, UO 2 [CO 3 ] 3 4-), for example, is difficult at pH 8.5 [40,41]. Overall, TRLFS is not suitable at present for determining U speciation in freshwater at high pH or estuarine and seawater.…”
Section: Watermentioning
confidence: 99%